Towards supply chain sustainability: economic, environmental and social design and planning. (15th October 2015) - Mota, Bruna; Gomes, Maria Isabel; Carvalho, Ana; Barbosa-Povoa, Ana Paula
Abstract: Costumers and governments are pressuring companies to become more sustainable. However, the lack of research on how to incorporate these issues makes this a challenging task. To fill this gap a generic multi-objective mathematical programming model for the design and planning of supply chains, integrating the three dimensions of sustainability is presented. The economic pillar of sustainability is addressed in this work considering the costs of the supply chain. Then ReCiPe, an environmental assessment methodology, indicated in the literature and by the European Commission as the most developed one currently available, is for the first time applied to supply chain design optimization. Finally, a social indicator appropriate to assess strategic decisions is proposed. This social indicator considers the impact of social and political concerns on company's performance. The relevance of this model as a decision support system is highlighted with its application to a real case study of a Portuguese battery producer and distributor. A set of strategies to select the best solution among the obtained optimal ones is presented. Results show that the model allows improvements in all the three dimensions of sustainability and offers important managerial insights. Highlights: Multiobjective mathematical programming model for supply chain design and planning. Integrates the three dimensions of sustainability. ReCiPe is applied in supply chain design optimization. A social indicator to assess strategic decisions is proposed. The model is applied to a real case study of a Portuguese battery producer.